الآراء التربوية لابن الجوزي في مرحلة الطفولة - Fahmi Ridha (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2019)
This research aims to my study on Imam Ibn Al-Jawzi’s ideas and educational views, especially in childhood at different levels, and trying to uncover the most important benefits that lie through it, hoping that it will be a starting point in the research on childhood education in our modern era. The approach that the researcher took in accomplishing writing this scientific research is the qualitative and descriptive research approach, and it is done through looking at Ibn Al Jawzi’s books for being the primary source and other references related to the topic. The researcher concluded the most important educational views of Ibn Al-Jawzi in early childhood (2) (2 - 6 years), which is the necessity of forming good habits and good manners at this stage, while continuing to root them in various methods of enticing and endearing, and the necessity to pay attention to values and ethics in years. The first age of the child, and the need for the educator to know the characteristics of the child's development at this stage, and the appropriate Islamic educational applications, and to preserve the personality of both the male and the female, by distinguishing the two teams by dressing, preparing and training on special work for each of them, and caring for physical, health, moral and social educationFor children, and the definition of parents with their great role in raising and raising children, taking into account wisdom in treatment and discipline, and caring for choosing good companionship for the child, because of its great impact in instilling good behaviors and ethics, and attention must be paid to the use of Islamic education methods and methods, and the need to diversify the methods of education in order to suit the nature of the soul Humanity, the need to pay attention to the basic sciences of the child, and present them on the less important sciences, and not to move from science to science until after the first science has been mastered, and the need to associate science with work with it, the need for diversity in science, and not confine to one science, taking into account For individual differences between children in their mental abilities, their learning and their behavior, the necessity to take care of educational curricula in the regular and pre-school stages, and focus on Islamic core subjects.